Examine digital maturity in construction supply chain - Tay, Gordon Zhi Wei (2023)
The construction supply chain is a network of organizations that work together to procure and deliver a built asset. The application of digital technologies to this supply chain is advancing rapidly, and maturity models can be used to assess an organization's level of capability in this regard. This research examines the digital maturity level of the construction supply chain in Malaysia. Seven digitalization dimensions synthesize from the reviewed literature are: digital strategy, digital organization, digital training, digital metrics, digital technology, digital culture, and utilization of BIM. A questionnaire consists of 21 closed ended questions covering these dimensions and another three open ended questions was used to collect the primary data from 163 respondents. The results analyzed with correlation, independent samples, and related samples tests concluded that the construction supply chain maturity in Malaysia is significantly higher than average (3.4 on a 5.0 scale). Digital technology leads the four pillars of digital maturity, the other three pillars are digital strategy, digital organization, and digital training. The research also found that experience and company size are two significant demographic attributes affecting the digital maturity of the company. The relationship between company size and digital maturity is not linear. However more experienced respondents were more likely to be digitally mature in most of the case. The findings of this research can help industry leaders understand the factors that contribute to digital maturity, the governing bodies to develop policies and regulations that support digital transformation and researchers and academics to develop new theories and models of digital maturity.